Salivary gland histology of the larva red palm weevil, Rhynchophorus ferrugineus (coleoptera: dryophthoridae) - Norzainih J.J.,; Nurul Wahida O., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Red Palm Weevil (RPW), Rhynchophorus ferrugineus (Olivier 1790) is a very destructive phytophagous insect pest to plants under family Arecaceae. The remarkable abilities of RPW to destroy the host plant have been attributed to its feeding behaviors and the functions of the salivary gland. The study describes the salivary gland histology of the larva RPW to assist in understanding the feeding habits of the pest. The observation was done by using light microscopy of Zeiss Image Analyzer with Axio Vision and Zeiss Axioscope with iSolutionlite softwares. RPW salivary gland tissues were stained with haematoxylin and eosin stains. Our study revealed, a unique ring-shaped acinar gland that encircled the crop of the larva. The two halves of the gland are long, wide and flatten leaf-like structures. The acini found are of different sizes and consist of two cell types, the zymogen and parietal cell. The cellular features observed suggest that the zymogen cells and parietal cells play different roles in salivary gland regulations. The results also revealed that the gland is heavily tracheated which might support the active feeding of the pest. The findings of the study could aid on preliminary understanding on the vigorous feeding of RPW larva that silently killing the host plant inside out.